SYNTHESIS 4-NITRO-41’-BIPHENYL BY CROSS-COUPLING REACTION - Vasiljević, Lj.; Ćirić, I.; Grujić, D. (Journal of Engineering & Processing Management, 2014)
Biphenylsarean important class of organic compounds. Theyare importantin the field of natural products, polymersand the contemporary medical materials. Synthetic route cross-coupling (Suzukis) reaction, starting from benzenevia the iodoniumsaltto 4-nitro-4’-metilbiphenyl is chosen in this study. The resulting intermediates and final product of the synthesis was confirmed by determination of the melting point and infrared spectroscopy. The final product was confirmed by NMR spectroscopy. This synthetic pathway to obtain biphenyls, which may be a key intermediate in many syntheses, there area number of advantages over the previously-defined synthetic routes due to the tolerance in respect of a wide range of functional groups, regio and stereoselectivity and specificity. In addition, theinorganic productsin the synthesis of non-toxic so farbeen used as heavy metals (Hg (II), Tl(III), Pb(IV)) and can be easily separated. High yields of the reaction products are obtained.